1986
DOI: 10.3354/meps032259
|View full text |Cite
|
Sign up to set email alerts
|

Microbenthos, meiobenthos and fiddler crabs: trophic interactions in a tropical mangrove sediment

Abstract: Aspects of the feeding ecology of Uca vocans and Uca polita from tropical mangroves were studied. Gut analysis revealed that microheterotrophs were the major food source for both species although U. polita also ingested small numbers of microalgae. No evidence was found for the ingestion of meiobenthos. Based on measurements of feeding rate and mass of feeding pellets produced it is estimated that the U. vocans population forages 43 % of the sediment surface during a low-tide feeding period of 2 to 2.5 h. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0
3

Year Published

1988
1988
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(55 citation statements)
references
References 27 publications
2
48
0
3
Order By: Relevance
“…It was, therefore, not surprising to find that irrespective of season, bacteria contributed to the diet of all ocypodid species collected in LRE. The use of bacteria as a food source by ocypodid crabs has been reported previously (Dye & Lasiak 1986, Meziane et al 2000, Takeda et al 2004). Nevertheless, it has been suggested that the bacterial marker, 18:1ω7 can be formed in vivo by chain elongation of dietary 16:1ω7 in some marine invertebrates, including crabs (Styrishave et al 2000, Stevens et al 2004 and reference therein).…”
Section: Food Sources Of the Crabsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was, therefore, not surprising to find that irrespective of season, bacteria contributed to the diet of all ocypodid species collected in LRE. The use of bacteria as a food source by ocypodid crabs has been reported previously (Dye & Lasiak 1986, Meziane et al 2000, Takeda et al 2004). Nevertheless, it has been suggested that the bacterial marker, 18:1ω7 can be formed in vivo by chain elongation of dietary 16:1ω7 in some marine invertebrates, including crabs (Styrishave et al 2000, Stevens et al 2004 and reference therein).…”
Section: Food Sources Of the Crabsmentioning
confidence: 99%
“…Ocypodid and grapsid crabs are the predominant organisms of the macrofauna in many mangrove ecosystems (Crane 1975, Macintosh 1988. The ocypodid crabs, with wider habitat preferences than those of the grapsids (which are usually limited to vegetated areas), are thought to be deposit-feeders and therefore rely more on sediment microorganisms for their nutritional needs (Dye & Lasiak 1986. However, these opportunistic species have also been reported to supplement their diets by ingesting vascular plants detritus and macroalgae (Meziane & Tsuchiya 2000, Hsieh et al 2002.…”
Section: Introductionmentioning
confidence: 99%
“…This contribution of diatoms was conagreement with those obtained in a Queensland mud-'firmed by low C:N ratios (Table 4). bank (Australia) by Dye & Lasiak (1986), who showed During the rainy season, the elevated contribution of that microheterotrophs were the major food source for 18:2w6 and 18:3w6 at Stn OB 3 (Table 3) could be ex-2 crabs of the Uca genus. However, Marguillier et al plained by the abundance of Enteromorpha intestinalis (1997) concluded that U. lactea fed mostly on a mixture on and around this station (pers.…”
Section: Fatty Acid Markers In Macrozoobenthosmentioning
confidence: 99%
“…Verwey, 1929;Gerlach, 1958;Macnae, 1968). More recent ecological studies mainly deal with burrowing crabs from the intertidal (Dye and Lasiak, 1986;Robertson, 1986;Warren and Underwood, 1986;Macintosh, 1988;Robertson and Daniel, 1989;Micheli et al, 1991;Smith et al, 1991). Burrow construction and maintenance, ventilation and import of organic matter may play a significant role in the energy flow and element cycling in shallow coastal systems (for a review with respect to tropical ecosystems see Alongi, 1989).…”
Section: Introductionmentioning
confidence: 99%